Reduction of malaria transmission by transgenic mosquitoes expressing an antisporozoite antibody in their salivary glands. Issue 1 (26th November 2012) - Sumitani, M.; Kasashima, K.; Yamamoto, D. S.; Yagi, K.; Yuda, M.; Matsuoka, H.; Yoshida, S.
Abstract: We have previously developed a robust salivary gland‐specific expression system in transgenic Anopheles stephensi mosquitoes. To establish transgenic mosquito lines refractory to Plasmodium falciparum using this system, we generated a transgenic mosquito harbouring the gene encoding an anti‐ P. falciparum circumsporozoite protein (PfCSP) single‐chain antibody (scFv) fused to DsRed in a secretory form (mDsRed‐2A10 scFv). Fluorescence microscopy showed that the mDsRed‐2A10 scFv was localized in the secretory cavities and ducts of the salivary glands in a secreted form. To evaluate P. falciparum transmission‐blocking in a rodent malaria model, a transgenic Plasmodium berghei line expressing PfCSP in place of PbCSP (PfCSP/Pb) was constructed. The PfCSP/Pb parasites were able to bind to the mDsRed‐2A10 scFv in the salivary glands of the transgenic mosquitoes. Importantly, the infectivity of the transgenic mosquitoes to mice was strongly impaired, indicating that the parasites had been inactivated. These results suggest that salivary gland‐specific expression of antisporozoite molecules could be a promising strategy for blocking malaria transmission to humans.